Pengaruh Latihan Ketepatan dan Kekuatan Terhadap Efektifitas Teknik Dasar Shooting Cabang Futsal Pada Kegiatan Ekstrakurikuler Di SMPN 2 Kutawaluya Karawang (Peneliti.net, 2022)
Strength training and accuracy are very important for futsal athletes to improve kick accuracy with repeated training so athletes can get maximum results. This researcher aims to determine the effect of precision and strength training on the basic effectiveness of shooting futsal in futsal extracurricular activities at SMPN 2 Kutaluya Karawang. This study uses an experimental method with a quantitative approach. The number of samples was 25 students in futsal extracurricular, and this research used purposive sampling technique. The instrument in this study used a goal shot. data analysis with normality, homogeneity and T test. There is a significant effect of strength training and punctuality of futsal at SMPN 2 Kutawaluya, proven correct with the results of the calculation of t count > t table, namely 13,201 > 2,064. From the results of the mean pretest and posttest, it is known that the mean pretest is 10.08 and the posttest is 15.4, (an increase of 5.32%) so that there is an increase in the percentage of 52.78% so that the alternative hypothesis (Ha) is accepted